Peran Lembaga Swadaya Masyarakat (LSM) Konsorsium Lingkungan Hidup dalam Menanamkan Perilaku Ramah Lingkungan Masyarakat Bantaran Sungai Surabaya - Ananda, Sarmela Dhea; Nugroho, Rivo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The KLH NGO is an organization consisting of community groups who are aware of environmental issues who are tasked with designing strategies for policies that are not environmentally friendly, socializing and coaching, environmental management, as well as empowering the community through environmental programs and providing policy input to the government. The aim of the research is to determine the role of KLH NGOs and to describe the supporting and inhibiting factors for the role of KLH NGOs in instilling environmentally friendly behavior in the communities along the Surabaya river. This research uses a qualitative approach with descriptive methods. The research subjects were six members of the KLH NGO and four members of the community. Data collection techniques were participant observation, in-depth interviews, and field notes and documentation. Research data was analyzed using data collection, data presentation and drawing conclusions then tested for truth value using credibility, transferability, debendability, observability, confirmability. The research results show that the KLH NGO plays a significant role in encouraging environmentally friendly behavior in Surabaya riverbank communities, by managing activities, reporting community issues, and influencing the development of aspects such as the availability of facilities, sustainable lifestyles, welfare partnerships, and sustainable living-based programs.